MIGRAIN RETINAL - Devi Ariani Sudibyo; Isti Suharjanti; Imas Resa Palupi (PERDOSNI, 2021)
Retinal migraine can affect serious complications in patients through persistent visual disturbances. It has been described as repeated monocular visual disturbances, including scintillations, scotoma, or blindness, accompanied by migraine headaches. Few journals and case reports discuss retinal migraine. We report a 23-year-old female presented with recurrent left headaches, which were preceded by visual disturbances in the form of scotoma, blurred vision and dark vision. Visual disturbances occurred in the left eye, lasting 5 to 15 minutes before headache. According to the 3rd edition of the International Classification of Headache Disorder (ICHD-3), the patient met the diagnostic criteria for retinal migraine. Flunarizine 10mg as a retinal migraine prophylactic medication gave good results. Keywords: flunarizine, headache, migraine, retinal, visual aura.